2017
DOI: 10.1007/s10943-017-0456-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hopelessness and Quality of Life in Patients with Heart Disease: An Example from Eastern Turkey

Abstract: This descriptive study was undertaken in order to determine hopelessness and quality of life among the patients with heart disease. No sampling was made, and 200 patients who were voluntary and were able to communicate were included in the study. The data of the study were collected using a personal information form that involved questions about patients' descriptive information and their diseases, Beck Hopelessness Scale and SF-36 Quality of Life Scale with a face-to-face interview technique. For the analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
8
0
3
Order By: Relevance
“…We also found that the age group of >73 reported lower QoL because of physical and emotional limitations that were reported compared to other age groups, such as 66-72 years old. This is an expected outcome that is also confirmed by the findings of other studies which showed that QoL is severely affected to the elderly population [ 9 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We also found that the age group of >73 reported lower QoL because of physical and emotional limitations that were reported compared to other age groups, such as 66-72 years old. This is an expected outcome that is also confirmed by the findings of other studies which showed that QoL is severely affected to the elderly population [ 9 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted in 2018, examined hopelessness and QoL of 200 patients with heart disease using the SF-36 QoL scale. It was found that elderly patients who suffered from CVD were affected negatively both physically and mentally, and as a result, they experienced decreased QoL [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the hopelessness levels of the 34-49 age group were higher (Table 2). Serafini et al (2020); Karakurt et al, 2018 andEfstathiou et al (2018) stated that hopelessness levels increased with age. With the advancement of age, the resistance of individuals against diseases may decrease, and their fight against the disease may become more difficult.…”
Section: The Mean Sos and Bhs Scores Of The Patients Based On Their Descriptive Characteristicsmentioning
confidence: 99%
“…En estudios subsecuentes donde se evalúe, también, la calidad de vida de los jóvenes, los ítmes podrían tener una relación inversa en el estado funcional, en el aspecto social, principalmente, y en la autoevaluación del estado de salud (Karakurt et al, 2017). Además, cabe resaltar que la disminución de los niveles de indefensión proporciona estrategias de afrontamiento de problemáticas relacionadas con la salud (Hernández & Landero, 2015) y su consecuente desmoralización ante la falta de cumplimiento de expectativas (Grassi et al, 2010).…”
Section: Discussionunclassified
“…En otro sentido, también se ha relacionado a la indefensión con la calidad de vida relacionada con la salud, debido a que se ha encontrado que es un predictor de la mortalidad después de una enfermedad crítica, con la percepción de funcionalidad y con calidad de vida (Orwelius, Kristenson, Fredrikson, Walther, & Sjöberg, 2017;Karakurt, Aşılar, Yildirim, & Memiş, 2017).…”
Section: Introductionunclassified